Analysis of Maternal Characteristics, Knowledge, and Perceptions Regarding Basic Immunization Completeness: A Cross-Sectional Study - Chairiyah, Royani; Setyaningsih, Widanarti (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Complete basic immunization is a government program aimed at protecting infants and children from preventable diseases. However, several factors cause mothers not to complete their children's immunizations. This study aimed to analyze the completeness of basic immunization based on maternal characteristics, knowledge, and perception. A quantitative cross-sectional study was conducted at the Simpang Empat Health Center, West Pasaman, from November 2023 to January 2024, involving 115 subjects. Results showed significant relationships between maternal education (p-value=0,004), employment status (p-value=0,036), religion (p-value=0,000), birth weight (p-value=0,000), and knowledge (p-value=0,044) with immunization completeness. No significant associations were found for birth order, number of children, family size, or perception. Religion also influenced immunization behavior. Strengthening family-based health promotion through KIA books, educational videos, and digital reminder applications is recommended.